Penerapan metode fuzzy analytical hierarchy process pada penentuan prioritas perawatan komponen jalan rel - Astuti, Septiana Widi; Septiyoko , Renaldy Yoga; Kurniawan, Muhammad Adib; Dewi , Puspita; Nopryanto, Windi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study uses the fuzzy analytical hierarchy process (FAHP) method to determine the maintenance priorities of railroad components on the section between Caruban Station - Babadan Station KM 155+000 to KM 157+200. FAHP was applied to evaluate and prioritize based on criteria including human resources, material, cost, risk, and level of damage, with participation from experts and academics. FAHP analysis showed that risk was the first-order criterion in priority assessment with a value of 0.31, followed by damage level with a value of 0.29, cost with a value of 0.17, material with a value of 0.14, and human resources with a value of 0.10. The resulting maintenance prioritization shows that ballast addition is the most urgent measure with the highest priority value of 0.54, followed by rail and sleeper maintenance with values of 0.27 and 0.18 respectively. The results of this analysis indicate a need for 1,456.60 m3 of additional ballast as a priority measure in the repair of railroad components in the studied segments.